IN BETWEEN AFFECTION, KNOWLEDGES, CONVERSATIONS AND STRUGGLES AROUND DISABILITY: AN INTERVIEW WITH LUCIANA FERRARI (PERcursos Linguísticos, 2024)
ABSTRACT: This interview sought to bring understandings about the term disability based on the experiences of Prof. Luciana Ferrari as a researcher on the connections between disability, language and decoloniality and as mother of Lívia, a teenager with cerebral palsy. The questions raised by Prof. Lívia Fortes, professor and researcher in the field of Applied Linguistics, more specifically on teacher education, started from her own process of constructing meanings about disability, intertwined with her personal relationship with Lívia and Luciana, of whom she is a close friend. We hope that the ideas presented and discussed here can lead to processes of interrupting the ableism that is so common in our society.KEYWORDS: Disability. Applied Linguistics. Ableism.
Keywords: Disability. Applied Linguistics. Ableism.